Why Are Constitutional Amendments in Mexico so Frequent? - George Tsebelis; Edwin Atilano-Robles (Journal of Politics in Latin America)
This research investigates the reasons for the overwhelming frequency of constitutional amendments in Mexico despite the widely held academic views of its constitution's rigidity. The article introduces a novel model highlighting the core of the Mexican Constitution. This model serves as a foundational lens to understand the interplay between political institutions, preferences of political actors, and amendment provisions. The application of this model attributes the frequency of amendments to three different reasons: first, the length and inconsistency of the Mexican Constitution; second, the institutional requirements for amendments; third, the political consensus prevailing in the Mexican political scene (crucial instances, such as the onset of multipartyism with concertacesión and pivotal reforms to Articles 27 and 73, offer deeper context) makes amendments feasible. A comprehensive analysis of the 68 constitutional amendments from 2000 to 2013 corroborates these expectations concerning institutional thresholds, coalition dynamics, and amendment significance.